Aesthetic regime change the Burnham plans and US landscape imperialism in the Philippines - Kirsch, Scott (Quezon City Ateneo de Manila University, 2017)
"Taking Daniel Burnham's 1904-1905 visit to the Philippines as a starting point, this article examines the unrealized dream of US colonial officials to extend American empire through the production of space, particularly the aesthetic dimensions or what might be called a landscape vision of US empire. It offers a brief but intimate history of the making of the Burnham plans for Manila and Baguio so as to better understand how the ideological contradictions of the imperial moment were built into American colonial spaces, sometimes brutally but sometimes through aesthetic means in the formation of setting and landscape."
Keywords: Burnham, Daniel H; W. Cameron Forbes; US Insular Government; Landscape architecture; City planning